2017
DOI: 10.1111/ctr.13104
|View full text |Cite
|
Sign up to set email alerts
|

Kidney retransplantation from HLA‐incompatible living donors: A single‐center study of 3rd/4th transplants

Abstract: Background: The demand for kidney retransplantation following graft failure is rising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The full-text review was undertaken for 886 eligible articles; of these 78 articles discussed HLA incompatibility at the level of the antigen mismatch only, 64-141 whereas 163 articles assessed incompatibility by molecular genotyping, molecular mismatch analysis, and/or pretransplant DSA verification by solid-phase and/or by cell-based assays. 3,142-303 The Preferred Reporting Items for Systematic reviews and Meta-Analyses diagram outlining the article selection process is provided in Figure 1. 304…”
Section: Resultsmentioning
confidence: 99%
“…The full-text review was undertaken for 886 eligible articles; of these 78 articles discussed HLA incompatibility at the level of the antigen mismatch only, 64-141 whereas 163 articles assessed incompatibility by molecular genotyping, molecular mismatch analysis, and/or pretransplant DSA verification by solid-phase and/or by cell-based assays. 3,142-303 The Preferred Reporting Items for Systematic reviews and Meta-Analyses diagram outlining the article selection process is provided in Figure 1. 304…”
Section: Resultsmentioning
confidence: 99%
“…The 5-year recipient survival was 82.5% for first, 100% for second, and 95% for third and fourth kidney transplantation. On comparing the living donor HLA incompatible versus the deceased donor compatible third and fourth transplantations, no statistical difference was seen in the allograft survival or estimated glomerular filtration rate at any time between the 2 groups [ 29 ]. All the aforementioned studies are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] As a result, some kidney transplant centers have lower kidney retransplant rates with highly selective criteria for retransplantation. 9,17,18 Nevertheless, kidney transplant patients, including recipients with kidney retransplant, are heterogeneous and there are many factors, including recipient, donor, and transplantrelated characteristics, that can result in varying outcomes. [2][3][4][5][6]19,20 Machine learning (ML), a subfield of artificial intelligence, has been applied to create clinical decision support tools and individualize patient care, including in kidney transplantation.…”
Section: Data From the United States Renal Data System And Canadianmentioning
confidence: 99%
“…However, prior studies have demonstrated an association between retransplantation and poor outcomes after kidney transplantation, including acute rejection, and reduced allograft survival, when compared to first kidney transplantation 12–16 . As a result, some kidney transplant centers have lower kidney retransplant rates with highly selective criteria for retransplantation 9,17,18 . Nevertheless, kidney transplant patients, including recipients with kidney retransplant, are heterogeneous and there are many factors, including recipient, donor, and transplant‐related characteristics, that can result in varying outcomes 2–6,19,20 …”
Section: Introductionmentioning
confidence: 99%